2022
DOI: 10.3389/fnut.2021.781333
|View full text |Cite
|
Sign up to set email alerts
|

Vitamins and Helicobacter pylori: An Updated Comprehensive Meta-Analysis and Systematic Review

Abstract: BackgroundOver recent decades, epidemiological studies have shown relationships between vitamins and Helicobacter pylori (H. pylori) infection and eradication, but the results are controversial.MethodsA comprehensive meta-analysis and systematic review were conducted to clarify the relationships between common types of vitamins and H. pylori. We applied meta-regression, subgroup analysis and sensitivity analysis to obtain available evidence. Articles published from January 1991 to June 2021 in PubMed, EMBASE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 80 publications
1
10
0
1
Order By: Relevance
“…Also, one of the Meta-analyses (consisting of 48 studies) demonstrated the association of the vitamins (e.g., vitamin D) and H. pylori . The results of this Meta-analysis suggested that the H. pylori positive patients had lower serum vitamin D levels than H. pylori negative patients ( 25 ). Both the factors, i.e., Dengue fever and H. pylori , lower the vitamin D levels in patients.…”
Section: Introductionmentioning
confidence: 90%
“…Also, one of the Meta-analyses (consisting of 48 studies) demonstrated the association of the vitamins (e.g., vitamin D) and H. pylori . The results of this Meta-analysis suggested that the H. pylori positive patients had lower serum vitamin D levels than H. pylori negative patients ( 25 ). Both the factors, i.e., Dengue fever and H. pylori , lower the vitamin D levels in patients.…”
Section: Introductionmentioning
confidence: 90%
“…However, after H. pylori eradication, the malnutrition in vitamin B12 levels could be restored (SMD = 1.85; 95% CI: 0.81–2.90). Although studies summarizing changes in the levels of vitamin A, C, and E in relation to H. pylori eradication success or failure are limited, interventions involving antioxidant vitamins C and E have shown significant improvements in the H. pylori eradication rate (relative risk (RR) = 1.25; 95% CI: 1.06–1.47), 38 while the impact of vitamin A remains unclear.…”
Section: Metabolic Pathways Alterationsmentioning
confidence: 99%
“…A comprehensive analysis of the NHANES III database revealed an inverse correlation between vitamin D deficiency (defined as levels lower than 20 ng/mL) and H. pylori CagA seropositivity. In a recent meta-analysis comprising 48 studies conducted in 2022, it was demonstrated that successful eradication of H. pylori was associated with higher serum vitamin D levels (standardized mean difference (SMD) = 1.37; 95% CI: 0.37-2.38), 38 while vitamin D deficiency was more prevalent in patients with treatment failure compared to successful treatment (70% vs. 30%). 39,40 Studies using mouse models have shown that oral supplementation of Vitamin D3 can reduce the rate of H. pylori colonization by upregulating key adherence markers such as CAMP expression in the gastric mucosa.…”
Section: Vitamin Metabolismmentioning
confidence: 99%
“…Vitamin C is an essential nutrient in humans and is involved in the regulation of a number of biological mechanisms, including iron metabolism, collagen and carnitine synthesis, catabolism of tyrosine and demethylation of proteins, DNA and RNA, and it also exerts both antioxidant and pro-oxidant activity at micromolar and millimolar concentrations, respectively [ 8 ]. Vitamin C might have antineoplastic effects in the stomach by reducing oxidative stress and subsequent cellular and DNA damage [ 9 ], inhibiting the formation of N-nitroso compounds and other carcinogens [ 10 , 11 ], and potentially interfering with Helicobacter pylori infection, which is recognized as the main risk factor for GC [ 6 , 12 ].…”
Section: Introductionmentioning
confidence: 99%